Evaluation of effective section for standard prestress concrete sections under flexure - Abdul Rahman, Ahmad Rosli (2005)
A study on the analysis and design of prestressed concrete standard bridge beams sections and calculation done using Microsoft Excel 2000 is presented. Standard sections shapes and sectional properties are selected and determined from available standard bridge beams section series and are grouped into the I-,T-, inverted T, U-, box and Y-beams type. All types of the standard bridge beam shape were analyse to the smallest dimension or size that can sustained the standard loads (service and ultimate loads) and comply to the limiting criteria i.e.deflection, shear, compressive and tensile stress. This was applied in the spreadsheet programs to determine the limits of prestress force and eccentricity, prestress force losses, cable zone, moment ultimate and moment of resistance,shear and deflection. A study and analysis were carried out on the smallest standard sectional dimension in the standard beam type series under various spans, its sectional properties, strength and physical, to determine the most efficient and economical section in term of the amount or cost of concrete and steel tendons.